Analysis of risk factors for urinary tract infection and bleeding after retrograde flexible ureteroscopy for stone removal - Guo, Tao; Zhang, Jiaen; Gao, Wenzhi; Ma, Yixiang (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to explore the risk factors for urinary tract infection (UTI) and bleeding after retrograde flexible ureteroscopy for stone removal, in order to prevent these complications and improve surgical outcomes.MethodsA retrospective analysis was conducted on 214 patients who underwent retrograde flexible ureteroscopy for kidney stones and ureteral stones from January 2015 to August 2022, with 135 patients having complete data. Clinical data, perioperative data, and stone characteristics were collected. Univariate and multivariate logistic regression analyses were performed to identify risk factors for UTI and bleeding after retrograde flexible ureteroscopy for stone removal.ResultsThe UTI rate after retrograde flexible ureteroscopy for stone removal was 8.15% (11/135), and the bleeding rate was 11.85% (16/135). Factors such as length of hospital stay (p = 0.034), stone size (p < 0.001), and preoperative creatinine (p = 0.016) were identified as risk factors for UTI after retrograde flexible ureteroscopy. Stone size (p = 0.004) was an independent risk factor for post-operative UTI. Stone size (p < 0.001), operation time (p < 0.001), and preoperative creatinine (p = 0.023) were risk factors for bleeding after retrograde flexible ureteroscopy. Stone size (p < 0.001) and operation time (p = 0.024) were independent risk factors for post-operative bleeding.ConclusionStone size is an independent risk factor for UTI after retrograde flexible ureteroscopy for stone removal, while both stone size and operation time are independent risk factors for bleeding after the procedure.